2018
DOI: 10.1590/s1517-707620180002.0351
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización del comportamiento frente a la corrosión en soldaduras de recargue de aceros inoxidables superdúplex

Abstract: RESUMENLos aceros inoxidables superdúplex poseen una estructura dual con un 50% de ferrita y austenita. Con este balance de fases se obtienen las mejores propiedades mecánicas y de resistencia a la corrosión. Gracias a estas características su empleo se encuentra en crecimiento, fundamentalmente, en las industrias del papel, químicas, del gas y del petróleo. La soldadura de recargue, o cladding, está asociada a la deposición de material superficialmente y es utilizada habitualmente tanto para la fabricación co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The results indicated that the cooling rate and number of filled weld layers significantly influenced the corrosion behavior. Therefore, when welding clad plates, it is recommended to use a faster welding speed and fewer filled weld layers (Zappa et al, 2018). Chen et al studied the transition layer specimens of 304 L/ SA516Gr70 welded joints by chemical immersion and electrochemical corrosion methods.…”
Section: The Welding Performance Of Stainless-clad Bimetallic Steelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the cooling rate and number of filled weld layers significantly influenced the corrosion behavior. Therefore, when welding clad plates, it is recommended to use a faster welding speed and fewer filled weld layers (Zappa et al, 2018). Chen et al studied the transition layer specimens of 304 L/ SA516Gr70 welded joints by chemical immersion and electrochemical corrosion methods.…”
Section: The Welding Performance Of Stainless-clad Bimetallic Steelsmentioning
confidence: 99%
“…When stainless-clad bimetallic steels are used in ocean engineering, the welding performance is an important factor that must be considered (Zhu et al , 2021; Yu et al , 2020; Zappa et al , 2018; Zhao et al , 2021; Meng et al , 2019). Many high-efficiency preparation processes for SCBS have been developed; however, there are many key barriers to its welding and joining procedure for the microstructural deterioration and excessive internal stress between two component metals.…”
Section: The Welding Performance Of Stainless-clad Bimetallic Steelsmentioning
confidence: 99%